(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article considers mnemotoponymic phraseological units of the modern French language, i.e. the phraseological units which include topocomponents which not only are used for geographical objects naming but also have apparent cultural-historical or socio-economic associations performing memorial function. The term mnemotoponym (Greek mnêmê - “memory”) is suggested for their core component naming. Mnemotoponyms within French phraseological units are subdivided according to their origin into autochthonous (e.g. l’enfer de Verdun, ça tombait comme à Gravelotte) and allochthonous (un procès de Moscou, aller à Baden-Baden). It is also suggested to classify mnemotoponymic phraseological units by their event indication, i.e. those events captured by historical memory in the metaphorical core of a certain phraseological unit. Those may be glorious military victories and inglorious defeats, large-scale disasters, major and minor events in the history of France and the whole world: soldats de Valmy, le soleil d’Austerlitz, c’est la Bérézina, soûl comme toute la Pologne, souvienstoi du vase de Soissons, le débarquement de Normandie, partir à Tataouine, Paris brûle-t-il? etc. The aim of the article is to estimate the layer of these phraseological units and demonstrate the possibility of their classification, present their potential in terms of historical memory manifestation and translation through the French phraseological fund. Key words: mnemotoponym, mnemotoponymic phraseological unit, the French language, historical memory. DOI 10.18522/1995-0640-2020-3-84-92